2012
DOI: 10.1016/j.mrfmmm.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TCHQ-induced genotoxicity and mutagenesis using the pSP189 shuttle vector in mammalian cells

Abstract: a b s t r a c tTetrachlorohydroquinone (TCHQ) is a major toxic metabolite of the widely used wood preservative, pentachlorophenol (PCP), and it has also been implicated in PCP genotoxicity. However, the underlying mechanisms of genotoxicity and mutagenesis induced by TCHQ remain unclear. In this study, we examined the genotoxicity of TCHQ by using comet assays to detect DNA breakage and formation of TCHQ-DNA adducts. Then, we further verified the levels of mutagenesis by using the pSP189 shuttle vector in A549… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A recent study investigated the mutagenicity of tetrachlorohydroquinone (TCHQ) using the supF shuttle vector system. The results indicated that TCHQ is a potent mutagen, with the majority (above 85%) being single-base mutations . The Ames assay (or the bacterial reverse mutation assay) is a standard method used for detecting the mutagenic potential of testing compounds .…”
Section: Toxicity Assessment Of Hbqsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study investigated the mutagenicity of tetrachlorohydroquinone (TCHQ) using the supF shuttle vector system. The results indicated that TCHQ is a potent mutagen, with the majority (above 85%) being single-base mutations . The Ames assay (or the bacterial reverse mutation assay) is a standard method used for detecting the mutagenic potential of testing compounds .…”
Section: Toxicity Assessment Of Hbqsmentioning
confidence: 99%
“…The results indicated that TCHQ is a potent mutagen, with the majority (above 85%) being single-base mutations. 64 The Ames assay (or the bacterial reverse mutation assay) is a standard method used for detecting the mutagenic potential of testing compounds. 65 On the basis of Ames tests, DCBQ, DCMBQ, TriCBQ, and DBBQ appear to be mutagenic (unpublished work).…”
Section: Hbq-induced Oxidative Stressmentioning
confidence: 99%
“…Genotoxicity can be due to many physico-chemical agents that result in a wide variety of possible damages to the genetic material, ranging from various DNA adducts to single-and double-strand breakages, DNA-DNA and DNA-protein cross-links or even chromosomal breakage (Ogura et al, 2008;Cavalcanti et al, 2010;Wang et al, 2012). The major challenge in genotoxicity testing resides in developing methods that can reliably and sensibly detect either such a vast array of damages or a general cellular response to genotoxic insult.…”
Section: Part A: Methods For Genotoxicity Assessmentmentioning
confidence: 99%
“…In addition, the pSP189 shuttle vector of A549 human lung carcinoma cells was also used to further confirm the level of mutagenesis. 74 TCHQ was found to induce significant genotoxicity through the breakage of DNA strand and formation of DNA adduct. As shown in Table 1, DNA damage measured in the comet assay showed that more DNA breakage was induced by increasing concentration (10−50 μM, 1 h) of TCHQ.…”
Section: Genotoxicity and Mutagenesis Induced Bymentioning
confidence: 99%
“…Therefore, the comet assay, which can detect the DNA breakage and the formation of TCHQ-DNA adducts, was used to measure TCHQ genotoxicity. In addition, the pSP189 shuttle vector of A549 human lung carcinoma cells was also used to further confirm the level of mutagenesis …”
Section: Genotoxicity and Mutagenesis Induced By Tchq In Mammalian Cellsmentioning
confidence: 99%